Effects of intravenous immunoglobulin on clinical and immunological findings of patients with humoral immunodeficiency diseases - Ersoy, Fügen; Tezcan, İlhan and Sanal, Özden (The Turkish Journal of Pediatrics, 1992)
We evaluated nine patients with humoral immunodeficiency (6 immunodeficiency with hyper-IgM, 2 X-linked agammaglobulinemia, 1 common variable immunodeficiency) who were being treated with intravenous immunoglobulins (IVIG). After the use of the IVIG regimen in a dose of 250-300 mg/kg/4 weeks for one year, the severity and frequency of infections, even in patients with chronic lung disease, decreased significantly. An improvement in pulmonary function tests was observed in four patients who had airway obstruction prior to IVIG therapy. Side effects such as chills and fever were observed in 21 of 91 infusions, particularly in the early months of therapy. Preinfusion administration of aspirin and diphenhydramine prevented these side effects. The inversion of the CD4⁺/CD8⁺ ratio was detected in most patients during both intramuscular gammaglobulins (IMIG) and IVIG therapy.